2005
DOI: 10.1111/j.1365-3059.2005.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in pathogen aggressiveness within a metapopulation of the Cakile maritimaAlternaria brassicicola host–pathogen association

Abstract: Variation in aggressiveness and its consequences for disease epidemiology were studied in the Cakile maritima–Alternaria brassicicola host–pathogen association. Variability in pathogen growth rates and spore production in vitro, as well as disease severity and lesion growth rate on C. maritima in glasshouse inoculation trials, were investigated. Substantial variation was found in growth rates among individual A. brassicicola isolates, as well as among pathogen populations. A significant trade‐off also existed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
7
24
0
Order By: Relevance
“…Pusz (2009) found colony diameter ranging from 4.8 to 6.8 cm while working with A. alternata. Similar observations were also recorded by Thrall et al (2005) and Rai and Kumari (2009).…”
Section: Discussionsupporting
confidence: 77%
“…Pusz (2009) found colony diameter ranging from 4.8 to 6.8 cm while working with A. alternata. Similar observations were also recorded by Thrall et al (2005) and Rai and Kumari (2009).…”
Section: Discussionsupporting
confidence: 77%
“…The mean minimum lesion size of 2.9 mm was observed in Am-17 and maximum of 10.2 mm was seen in Am-1. The findings are in agreement with Thrall et al (2005) who reported significant variations in the lesion size produced by Alternaria brassicicola isolates on wound inoculated Cakile maritima plants. Kumar (2004) also reported variation in lesion size and lesion number in Alternaria triticina isolates.…”
Section: Pathogenic Variabilitysupporting
confidence: 82%
“…Almost similar observations were recorded by Pusz (2009) on A. alternata with colony diameter ranging from 4.8 to 6.8 cm among 26 isolates after seven days of inoculation. Similar observations were also recorded by Thrall et al (2005) and Rai and Kumari (2009 …”
Section: Cultural Variabilitysupporting
confidence: 77%
“…The sites chosen for this study represent a subset of populations that form part of ongoing work on the metapopulation dynamics of the Cakile-Alternaria interaction (60,61). The collection, isolation, and maintenance of isolates were as described previously (60). Infected plants were sampled randomly within populations.…”
Section: Methodsmentioning
confidence: 99%